Associations among menopausal status, menopausal symptoms, and depressive symptoms in midlife women in Hunan Province, China. (3rd May 2020) - Fu, J.-X.; Luo, Y.; Chen, M.-Z.; Zhou, Y.-H.; Meng, Y.-T.; Wang, T.; Qin, S.; Xu, C.
Abstract: Objective: This study aimed to determine the associations among menopausal status, menopausal symptoms, and depressive symptoms in midlife women in Hunan, China. Methods: A secondary analysis involving 3199 women aged 40–55 years was performed based on data from the Women Health Needs Survey 2018 in Hunan Province, central south China. The depressive symptoms were determined using the 9-item Patient Health Questionnaire. The menopausal symptoms were assessed using the Kupperman Menopausal Index. Demographic characteristics and menopausal status were measured using self-administered questionnaires. Results: The prevalence of depressive symptoms was 19.3%. The three most common menopausal symptoms were insomnia (48.0%), fatigue (42.7%), and mood swing (39.8%). The increase in depressive symptoms was significantly associated with menopausal status and menopausal symptoms. After controlling for demographic variables, multivariate logistic regression showed that menopausal transition (odds ratio [OR] = 1.14, 95% confidence interval [95% CI] = 1.12–1.86), postmenopause (OR =1.52, 95% CI = 1.09–2.11), and four menopausal symptoms including mood swing (OR = 1.32, 95% CI = 1.03–1.70), depressive mood (OR = 2.28, 95% CI = 1.79–2.91), palpitations (OR = 1.37, 95% CI = 1.06–1.77), and urinary tract infection (OR = 1.49, 95% CI = 1.16–1.92) were associated with depressive symptoms. Conclusions: Independent of demographic variables, menopausal transition, postmenopause, and four menopausal symptoms (mood swing, depressive mood, palpitations, and urinary tract infection) increase the risk of depressive symptoms.